The adults, larvae, and systematics of the Nearctic Oemopteryx Klapálek, 1902 (Plecoptera: Taeniopterygidae) - Verdone, Chris J.; Williams, Bronwyn W.; Beaty, Steven R.; Holland, Victor B.; Grubbs, Scott A.; Dewalt, R. Edward (Zootaxa, 2025)
The adult and larval life stages of the Nearctic species of Oemopteryx Klapálek, 1902 (Plecoptera: Taeniopterygidae) are reviewed using color images, scanning electron microscopy photomicrographs, variation in the barcode region of the mitochondrial DNA cytochrome c oxidase subunit I (COI) gene, and distributional information. Two new species are described from the southeast Nearctic region. Adult and larval keys to Oemopteryx species are presented in addition to revised keys to genera for Nearctic Taeniopterygidae.